DAMPAK TANDA TANGAN ELEKTRONIK TERHADAP KEAMANAN DAN KEPERCAYAAN DALAM TRANSAKSI DIGITAL: KAJIAN EMPIRIS DAN ANALISIS KEBIJAKAN DI INDONESIA - Athaya Naila Ayasha Trishadiatmoko (Media Bina Ilmiah, 2025)
In the era of rapid digital transformation, electronic signature comes as an alternative solution that offers efficiency, speed, and security in digital transactions. This article analyzes the effect of electronic signature on the security and trust aspects of digital transactions in Indonesia through a functional equivalence approach with conventional signatures. The study highlights the three main pillars of functional equivalence, namely authentication, integrity, and non-repudiation, and discusses the challenges of electronic signature implementation in terms of legal regulations, technological infrastructure, and public literacy levels. The results show that although electronic signature has a legal framework through the Electronic Information and Transactions Law and cryptographic technology support, its implementation still faces significant barriers. Collaboration between the government, industry players, and the community is needed to build a safe and reliable digital ecosystem. This study recommends harmonizing regulations, increasing public education, and strengthening cybersecurity to increase the adoption of electronic signature in Indonesia.